Impact of α-linolenic acid supplementation on long-chain n-3 fatty acid profiles in Western, flexitarian, vegetarian, and vegan diets - Klein, Lea; Kipp, Kristin; Lorkowski, Stefan; Eichelmann, Fabian; Dawczynski, Christine (Frontiers in Nutrition, 2025)
IntroductionLong-chain (LC) n-3 polyunsaturated fatty acids (PUFA) are critical nutrients in vegetarian and vegan diets due to the absence of fish and other animal products. α-Linolenic acid (ALA) is the main plant derived precursor for eicosapentaenoic acid (EPA), docosapentaenoic acid (DPA) and docosahexaenoic acid (DHA), yet conversion efficiency is limited and influenced by several dietary and metabolic factors. Therefore, the NuEva Study aimed to investigate the impact of flaxseed oil on fatty acid profiles depending on age, sex, body mass index (BMI), dietary pattern (Western diet (omnivores), flexitarian, vegetarian, vegan), and status of relevant nutrients.MethodsThe NuEva study is a prospective non-randomized intervention with parallel diet groups (Western diet (omnivores), flexitarian, vegetarian, vegan; n = 168), which includes nutrient-optimized menu plans (12 months) combined with flaxseed oil supplementation (3 g/d ALA for 9 months). Fatty acids were analyzed at baseline and repeatedly throughout the intervention period focusing on n-6 and n-3 PUFA in plasma and erythrocytes lipids. Furthermore, potential modulators of ALA conversion (age, sex, BMI, linoleic acid, arachidonic acid, and EPA status) were investigated.ResultsIn Western diet participants, erythrocyte n-6 PUFA increased by 5.5%, mainly due to arachidonic acid. In contrast, ALA (+22.5–38.4%), EPA (+27.3–40.7%), DPA (+27.2–40.7%) and DHA (+12.8–26.0%) increased significantly across all dietary patterns. Conversion efficiency was unaffected by sex, BMI, age, linoleic acid, or arachidonic acid, but individuals with low baseline EPA showed markedly greater increases in EPA (+62.9% vs. +12.9%), DPA (+41.9% vs. +22.3%), and DHA (+27.0% vs. +7.6%) compared to subjects with higher EPA status.ConclusionIn conclusion, flaxseed oil supplementation combined with a controlled diet effectively improves n-3 LCPUFA status irrespective of habitual diet. The extent of relative improvement was primarily determined by baseline EPA concentrations.